Caregiver Resilience and Burden in Long-Term Care Family of Children with Developmental Disabilities: A Cross-Sectional Study - Wulandari, Sarah Kartika; Sriwahyuningsih, LG Nita; Israfil, Israfil (Chakra Brahmanda Lentera Institute, 2026)
Background: A family with a child with special needs experiences a struggle to provide care and quality of life. However, empirical evidence on the relationship between resilience and caregiver burden in the long-term care of children with developmental disabilities (DDC) in low- and middle-income countries remains limited, with a family nursing perspective in Indonesia, especially in Bali. This study aimed to determine the relationship between caregiver burden and resilience in long-term care of children with developmental disabilities. Methods: This study was reported in accordance with the STROBE guidelines. A cross-sectional study was conducted online using network sampling DDC in Denpasar City. The questionnaires were the Burden Scale for Family Caregivers (BSFC) to measure the family burden as the independent variable and the Resilience Scale for Adults (RSA) used to measure the resilience of the caregiver as the dependent variable. Spearman’s rank correlation was used for data analysis. Results: As many as 102 parents or siblings of DDC joined the research online. Data showed most caregivers were mothers (67,6%), with more than one child (65,7%), and with various types of DDC. A moderate negative correlation was observed between caregiver burden and resilience (r = −0.294, p < 0.005). The higher burden experienced by siblings (mean= 13.5), when fathers have the highest resilience (mean= 99.83), as they felt less burden (mean= 8.93). Conclusion: The greater burden experienced by the family implied a lower capacity to express resilience. Coping skill training could be developed as a response to the burden to build better family coping and boost resilience.